Mathematical modeling of drying behavior of cashew in a solar biomass hybrid dryer - Dhanushkodi, S.; Wilson, Vincent H.; Sudhakar, K. (Elsevier Ltd, 2017)
The main objective of this study is to analyze the drying behavior of cashew nut experimentally in a solar biomass hybrid dryer using mathematical models. Suitability of fifteen different mathematical drying models available in the literature is used to describe the drying characteristics of cashew. Experimental data of moisture ratio, temperature and relative humidity obtained from different dryer conditions were fitted to the various empirical drying models. The performance of the drying model was compared based on their correlation co-efficient (R2), Root Mean Square Error (RMSE) and Reduced Chi-Square (χ2) between the observed moisture ratios. The two terms and Midilli models showed the best fit under solar drying. Page model was found to be the best model for describing the thin layer drying behavior of cashew for biomass drying and hybrid drying.